Physical activity of tourism and recreation students in terms of accressibility to open areas - Pasek, Marcin; Olszewski, Jacek (Turyzm/Tourism, 2017)
The aim of the article is to present the factors which affect the choice of place of recreation, as well as indicate the preferred forms of physical activity taken up there. The authors also discussed the relationship between distance from open areas and frequency of visits. Moreover, they evaluated current knowledge about the role of the natural environment as a physical recreation space. The research was conducted among a group of 305 physically active individuals (students of the Academy of Physical Education and Sport in Gdańsk), using questionnaires. The respondents defined the role of location in comparison to other motivational factors for a range of physical activities (recreation). They also spoke about their preferred forms of physical activity in the natural environment, compared to the roles of natural and human environments with regard to physical activity. They also provided an answer to the question whether an open area which does not provide respondents with an opportunity to undertake their favoured recreation would remain of interest. The study results demonstrate the unquestionable importance of having access to attractive natural surroundings with respect to physical activity. This allows a relation to be made between leisure in the natural environment and an improvement in the health of the physically active.